Identification of centrality of West Kalimantan tourist attractions based on network analysis - Syaiful Muazir; Riesa Rizki Amalia; Lestari Lestari; Muhammad Nurhamsyah; Muhammad Ridha Alhamdani; Mustikawati Mustikawati (Jurnal Pariwisata Pesona, 2024)
Tourism destinations represent a vital element and the primary motivator for tourists in determining their travel and visitation patterns. Consequently, it is essential to implement effective planning strategies that align with the diverse motivations of tourists. One of the scientific discussions in tourism planning or development is through network analysis. With network analysis, it can explain the relationship or relationship between tourist attractions so that in the future it can be further developed how the attraction cluster in a tourist destination can be developed and directed. This research sees that the priority in terms of centrality should be given to the many attractions in West Kalimantan. This study aims to identify relationships or relationships between tourist attractions in West Kalimantan to be able to see the trend of networking (centrality), can be in the form of centralization, connectedness, clusters, and others. This research uses a network analysis approach which in principle is divided into several methods such as centrality calculations carried out with analytical techniques/tools such as degree, closeness, betweenness, and eigenvector. From the results obtained, the cluster of tourist attractions spread evenly in each region. The tourist attraction cluster with the most interaction is located in Bengkayang Regency, Pontianak City, North Kayong Regency, Ketapang Regency, and Kapuas Hulu Regency. For tourist attraction clusters with easy access, they are in the Sambas Regency and Singkawang City areas. Clusters of tourist attractions that become hubs are located in Sanggau Regency and Ketapang Regency. Then the cluster of tourist attractions with the most central point is located in Singkawang City. The road network (access) in the configuration is very influential in the connectivity between regions in reaching tourist attractions